ASSESSMENT OF SEXUAL DESIRE IN PEOPLE LIVING WITH HIV IN ALBANIA: HOW CHANGE SEXUAL DESIRE ACCORDING TO ADHERENCE IN THERAPY, SEXUAL BEHAVIOR, DEPRESSION - Dudushi, Redona (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2018)
Introduction: After initiating antiretroviral treatment (ART) patients HIV positive, regain their health, so they seek to return to an active ’normal’ life, especially to sexual activity. The aim of the study is to assess the sexual desire in people living with HIV in Albania: how change sexual desire according to adherence in therapy, sexual behavior, depression. Material and Methods: A descriptive cross sectional study was conducted in outpatient clinic of people living with HIV in Albania. Two hundred sixty four patients were interviewed about their sexual identity, sexual orientation, sexual attraction, sexual practices, and their sexual partners using AMIS questionnaire (Emory University Instrument) to measure their sexual risk behaviors. Patients Health questioner PHQ-9 was used as a screening tool to identify depressive symptoms in HIV-infected patients. Also the sexual desire inventory (SDI), developed by Spector et. al., in 1996, was used to assess the sexual desire in HIV-infected patients. The data collected was analyzed using SPSS software. Result: Over all 264 patients’, median age for all patients was 43.4 ±11.7, and the predominance of patients was for male 73.1% compared to female 26.9%. 63.63% of them have a higher score (≥ 45) that reflect a higher level of sexual desire, meanwhile, those with low score (≤45) were only 36.37%. Cronbach Alfa 0.906 and a statistically significant correlation between the statements (p <0.001). Its high validity and re ability of instrument. We noted that adherence did not show any correlation with sexual desire. Patients with low sexual desire in a low therapy adherence presented the higher percentage (43.7%), compared to them with high therapy adherence (27.1%) or without therapy (29.2%). There are a significant association between the sexual desire and sexual orientation for p value p=0.03. In HIV patients, depression may play a role in sexual desire (p <0.0001 with a coefficient of -4.48173, -5.76898, and -5.44823 respectively). This indicates that there is a negative correlation between them, the higher of the depression degree manifest low sexual desire or vice versa a low depression degree manifests high sexual desire. Conclusion: In the conclusion, our study is the first to report assess the sexual desire in people living with HIV in Albania, and the change sexual desire according to adherence in therapy, sexual behavior and depression. 63.63% of HIV-infected patients have a higher score (≥ 45) that reflect a higher level of sexual desire; meanwhile, those with low score (≤45) were only 36.37% of participants. In the end, our findings presented a negative association between depression and sexual desire status of patients living with HIV. The higher of the depression degree manifest low sexual desire or vice versa a low depression degree manifests high sexual desire.